Important aspects of osteoarthritis therapy during the COVID-19 pandemic - A. M. Lila; A. G. Chuchalin; I. Yu. Torshin; O. A. Gromova (Современная ревматология, 2022)
Chronic systemic inflammation, which is significantly exacerbated by COVID-19 or in conditions of induced physical inactivity, has a great negative effect on the condition of patients with osteoarthritis (OA). Conversely, diseases associated with chronic inflammation (OA, obesity, hypercholesterolemia, bronchial asthma, diabetes mellitus, chronic kidney disease, deficiency of essential micronutrients, etc.) are the background for a more severe course of coronavirus infection. In patients with this comorbid background, infection with SARS-CoV-2 exacerbates chronic systemic inflammation through activation of the NLRP3 inflammasome with the involvement of toll receptors (TLRs). Inflammasome activation is the central mechanism for the formation of the so-called cytokine storm, which leads to pyroptosis of various cell types and the development of multiple organ pathologies characteristic of COVID-19. In addition, induced physical inactivity (immobilization stress) contributes to the development of sarcopenia and increased pain in OA. The chondroprotectors chondroitin sulfate, glucosamine sulfate, undenatured collagen inhibit TLR and inflammasome activation, inhibit muscle mass loss, and may exhibit a direct antiviral effect (inhibit the replication of the SARS-CoV-2 virus).